(untitled) (Quinto Sol, 2024)
This paper examines a series of media operations which took place between 1981 and 1982, with the aim of counteracting the impact of the denunciations made abroad by one of the victims of the dictatorship, Jacobo Timerman. The research investigates these operations, situating them within the framework of the so-called "psychological actions" and reconstructs the role played in these practices by General Ramón Camps, former chief of the Buenos Aires Province Police, who had been in charge of Timerman’s detention and clandestine captivity. In this line, the article studies the main topics, strategies and supports used, and the plots and actors involved in these actions, highlighting the participation of media entrepreneurs, journalists, politicians, members of the Catholic Church, members of the Jewish community, the military and the police.